Clinical Characteristics for Differentiating Febrile Children With Suspected Kawasaki Disease Diagnosis - Yan, Jia-Huei; Chang, Ling-Sai; Lin, Yi-Ju; Guo, Mindy Ming-Huey; Huang, Ying-Hsien; Kuo, Ho-Chang (Frontiers in Pediatrics, 2020)
Background: Kawasaki disease (KD) is a form of vasculitis that primarily affects children under the age of 5 years old. Patients may be missed or diagnosis delayed when initial clinical symptoms do not fulfill the traditional criteria or a normal echocardiography was found. In this study, we aimed to analyze factors that clinicians could use to differentiate febrile children suspected of KD. Method: We retrospectively enrolled in this study a total of 50 febrile children who were initially suspected of KD, but they did not meet the American Heart Association (AHA) criteria for a diagnosis. However, some of these patients were diagnosed with KD during their second visit. We analyzed patients' characteristics, clinical symptoms, and laboratory data (initial data in the first visit). Results: In total, 50 patients were enrolled in the study. Of those, ten patients were diagnosed with KD on their second visit (group 1), while the other 40 patients still did not fit a KD diagnosis (group 2). A higher neutrophil-to-lymphocyte ratio (NLR, p = 0.037) and higher C-reactive protein levels (CRP, p = 0.02) were found in group 1 when compared to group 2. A patient with a NLR >1.33 combined with a CRP more than 33 mg/L was more likely to have KD (Sensitivity 90%, specificity 69.2%, p = 0.001; Odds ratio 20.25, 95% confident interval 2.3–178.25). Conclusion: Among patients suspected of KD that did not initially meet the criteria, clinicians should pay special attention to elevated neutrophil-to-lymphocyte ratios and CRP levels and closely follow up such patients.